Calling in the CaValry—Toxoplasma gondii Hijacks GABAergic Signaling and Voltage-Dependent Calcium Channel Signaling for Trojan horse-Mediated Dissemination - Bhandage, Amol K.; Barragan, Antonio (Frontiers in Cellular and Infection Microbiology, 2019)
Dendritic cells (DCs) are considered the gatekeepers of the immune system but can, paradoxically, also function as Trojan horses to mediate dissemination of the obligate intracellular parasite Toxoplasma gondii. Here, we review the current knowledge on how Toxoplasma hijacks the migratory machinery of DCs and microglia. Shortly after active invasion by the parasite, infected cells synthesize and secrete the neurotransmitter GABA and activate GABA-A receptors, thereby making infected DCs hypermigratory in vitro and in vivo. The signaling molecule calcium plays a central role for this migratory activation as signal transduction following GABAergic activation is mediated via the L-type voltage-dependent calcium channel (L-VDCC) subtype Cav1.3. These studies have revealed that DCs possess a GABA/L-VDCC/Cav1.3 motogenic signaling axis that triggers migratory activation upon Toxoplasma infection. Moreover, GABAergic migration can cooperate with chemotactic responses. Additionally, the parasite-derived 14-3-3 protein (Tg14-3-3) has been associated with hypermigration of DCs and microglia. We discuss the interference of Toxoplasma infection with host cell signaling pathways that regulate migration. Altogether, T. gondii hijacks non-canonical signaling pathways in infected immune cells to modulate their migratory properties, and thereby promote its own dissemination.